Actividades con germoplasma de frijol. Colección, multiplicación y distribución de germoplasma - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
During 1986 the emphasis on the acquisition of Phaseolus germplasm continued to be directed to land races and wild species. In addition to intensive expeditionary work in Latin America, several interesting materials from Europe, Asia, and Africa were received. Of the last batch of 6000 new accessions approved by the Instituto Colombiano Agropecuario for multiplication in CIAT greenhouses and isolated fields, about 1100 materials were multiplied from 23 countries (mainly from USA, Peru, and Rwanda). Characterization of germplasm by plant habit and seed size, using the descriptors proposed by CIAT, continued to detect similar groups of germplasm. A duplicate of the base collection for preservation in long-term storage (2000 accessions) was sent to the Centro Nacional de Recursos Geneticos, Brazil. Four collection trips to Guatemala, Argentina, Peru, and Mexico were carried out by the genetic resources unit, of which the results and outstanding conclusions are presented. Future plans include the collection of germplasm in Costa Rica and the aforementioned countries and research on seed multiplication and morphoagronomic evaluation, especially for yield and adaptation. (CIAT)